18F-FDG PET-CT in Re-staging Post-operative Renal Cell Carcinoma: A Five-year Experience in INMAS Dhaka - Hossain, Sadia; Rahman, Farhana; Afrin, Rawnak; Hossain, Mohana; Sharmin, Shaila; Akhter, Afroza; Sultana, Tania; Biswas, Tanima; Hasan, Tanvirul; Rashed, Asif (Bangladesh Journal of Nuclear Medicine, 2025)
Background: Renal cell carcinoma (RCC) includes a wide variety of histopathologic subtypes. About 25–30% patients present with metastatic disease initially and 20%-40% patients later develop distant metastases. Accurate re-staging of disease as early as possible is crucial for optimum therapeutic decision and alters outcome of patients. F-18 FDG PET-CT plays a vital role in effective postoperative surveillance and restaging with high sensitivity, specificity, and accuracy. Materials & Methods: This prospective observational study included 67post-operative patients with renal cell carcinoma who were referred to Institute of Nuclear Medicine and allied sciences, Dhaka for an 18F FDG PET scan during the period of July, 2019 to July, 2024. PET-CT was performed with ‘Philips 128 slice ingenuity TF PET CT’ machine 60 minutes after intravenous administration of radiopharmaceutical. Semi-quantitative estimation of FDG uptake was performed by calculating SUVmax value, corrected for dose administered and body weight (g/ml). Results: 16 out of 22 patients with suspected metastases in other imaging modalities were positive in 18F FDG PET-scan. 22 new metabolically active distant metastatic foci without previous evidence were detected. 8 new locoregional recurrences were found. In total,35 patients had distant metastases in 114 foci among which lymph node (41 foci, comprising of 34 %) & lung (27 foci, comprising of 22.5 %) were the commonest sites. The other metastatic foci were present in adrenal glands (12 foci), peritoneum (7 foci), pleura (4 foci), bones (12 foci), soft tissue (8 foci), muscle (4 foci), liver (3 foci), brain (1 foci) & opposite kidney (1 foci). Conclusion: Our study was done to find the impact of 18F FDG PET-CT in restaging of post-operative cases due to RCC. Bangladesh J. Nuclear Med. 28(1): 18-21, 2025